MECHANISM OF RESTORATION OF THE DISPERSE FERRIFEROUS WASTE IN A DYNAMIC LAYER - S. L. Rovin (Литьë и металлургия, 2015)
Some results of researches of processes of heating and restoration of the disperse materials containing iron in laboratory and semi-industrial conditions and the mechanism (physical model) developed on the basis of the obtained data for the description of processes of solid-phase restoration of disperse ferriferous waste in a dynamic layer which can be considered as part of the solution of a task of development of technology of a low-tonnage recycling are presented in the article.Keywords. Recyclimg, the mechanism of solid recovery, dispersion metal wastes, rotary tilting furnaces.